Henry Bumstead and the World of Hollywood Art Direction - Horton, Andrew (University of Texas Press, 2010)
From a hotel in Marrakech inThe Man Who Knew Too Much,to small-town Alabama inTo Kill a Mockingbird,to Mission Control inSpace Cowboys,creating a fictional, yet wholly believable world in which to film a movie has been the passion and life's work of Henry Bumstead, one of Hollywood's most celebrated production designers. In a career that has spanned nearly seventy years, Bumstead has worked on more than one hundred movies and television films. His many honors include Academy Awards for Art Direction forTo Kill a MockingbirdandThe Sting,as well as nominations forVertigoandThe Unforgiven. This popularly written and extensively illustrated book tells the intertwining stories of Henry Bumstead's career and the evolution of Hollywood art direction. Andrew Horton combines his analysis of Bumstead's design work with wide-ranging interviews in which Bumstead talks about working with top directors, including Alfred Hitchcock, George Roy Hill, Robert Mulligan, and Clint Eastwood, as well as such stars as Paul Newman, Robert Redford, Doris Day, Jimmy Stewart, Sidney Poitier, Bill Cosby, Jerry Lewis, and James Cagney. Numerous production drawings, storyboards, and film stills illustrate how Bumstead's designs translated to film. This portrait of Bumstead's career underscores an art director's crucial role in shaping the look of a film and also tracks the changes in production design from the studio era through location shooting to today's use of high-tech special effects.